Pengaruh Regret Aversion Bias, Regret Aversion Bias, dan Risk Tolerance Terhadap Keputusan Investasi Generasi Z di Kota Batam - Paramitha Domingga Tambunan; Haposan Banjarnahor (Masyarakat Ekonomi Syariah Bogor, 2026)
This study aims to examine the influence of regret aversion bias, herding behavior, and risk tolerance on the investment decisions of generation z in Batam City. A quantitative approach was employed using primary data collected through questionnaires distributed to 100 generation z respondents who have prior investment experience, selected using a purposive sampling technique. The data were analyzed using multiple linear regression with the assistance of IBM SPSS version 26. The results indicate that, on a partial basis, regret aversion bias and herding behavior have a positive and significant effect on investment decisions, while risk tolerance does not show a significant effect. However, when tested simultaneously, all three variables have a significant impact on the investment decisions of generation z. Therefore, this study concludes that psychological and behavioral factors play an important role in shaping generation z’s investment decisions, particularly under conditions of market uncertainty.